Bullying and victimization among 8-year-old children: A 16-year population-based time-trend study. (June 2013) - Ilola, Anna-Marja; Sourander, Andre
<x xml:space="preserve">Abstract</x> Background: Bullying has been recognized as a major social and health problem among children. There are only few studies about changes in the prevalence of bullying behaviour, especially among younger children. Aims: To examine changes in the prevalence of bullying behaviour at three time-points, 1989, 1999 and 2005, among 8-year-old children living in south-western Finland. Methods: Three representative cross-sectional samples of 8-year-old children from south-western Finland were compared. All children born in 1981 (n = 1038), 1991 (n = 1035) and 1997 (n = 1030) and living in selected school districts were included in the study samples. The sampling, procedure and methods were similar at all three time-points. The participation rate varied from 84% to 96%. Children, parents and teachers filled in questionnaires asking about bullying and victimization. Results: In 2005, statistically significantly fewer boys were victimized than in 1989. Among girls, there was a decreasing trend of victimization but this was statistically significant only in parental reports. More girls were frequent victims in 2005 than in 1989. Among boys, the number of bullies also decreased. However, teachers found more bullies among girls in 2005 than in 1989. Conclusion: There was a slight decrease in bullying behaviour among boys from 1989 to 2005. The main finding among girls was an almost twofold increase in teacher-reported bullies (from 5% to 9%). Bullying and its prevention are major challenges for educational and school health services. Peer relationships and a non-violent school environment are major challenges of children's lives; therefore, continuous monitoring of bullying behaviour is important.